Impact of Truncated Area on Point Estimate and Intra-Subject Variability in Bioequivalence of Dutasteride with Long Half-Life - Prasaja, Budi; Harahap, Yahdiana; Lusthom, Windy; Yumi, Lia; Sofiana, Anna; Sandra, Monica; Safira, Falah; Chilmi, Uci (Drug research, 2018)
To investigate the effect of using truncated area under the curve (AUC ) on bioequivalence of dutasteride with long half-life in point estimate and intra-subject variability. Fifteen subjects were enrolled in this single-dose, open-label, randomized two-way crossover design following an overnight fasting with five-week washout period. Plasma samples were collected to 72 h and 144 h following drug administration and dutasteride were determined by liquid chromatography-tandem mass spectrometry (LC-MS/MS) methods. The pharmacokinetic parameters for bioequivalence assessment were AUC and AUC . The estimated point and the 90% confidence intervals were 91.07% (84.54-98.11%) for AUC and 91.43% (84.65-98.75%) for AUC , that is, within the ranges for acceptance of bioequivalence. The intra-subject variability's were 11.45% for AUC and 11.87% for AUC CONCLUSIONS: There was no statistically significant difference in point estimated and intra-subject variability between truncated AUC at 72 h and 144=h and the truncated AUC (AUC ) approach could be considered for bioequivalence assessment for dutasteride.